Measuring the semantic priming effect across many languages - Buchanan, Erin M; Cuccolo, Kelly; Heyman, Tom; van Berkel, Niels; Coles, Nicholas A; Iyer, Aishwarya; Peters, Kim; van 't Veer, A E; Montefinese, Maria; Maxwell, Nicholas P; Taylor, Jack E; Valentine, Kathrene D; et al. (Nature Human Behaviour, 2025)
Semantic priming has been studied for nearly 50 years across various experimental manipulations and theoretical frameworks. Although previous studies provide insight into the cognitive underpinnings of semantic representations, they have suffered from small sample sizes and a lack of linguistic and cultural diversity. In this Registered Report, we measured the size and the variability of the semantic priming effect across 19 languages (n = 25,163 participants analysed) by creating the largest available database of semantic priming values using an adaptive sampling procedure. We found evidence for semantic priming in terms of differences in response latencies between related word-pair conditions and unrelated word-pair conditions. Model comparisons showed that the inclusion of a random intercept for language improved model fit, providing support for variability in semantic priming across languages. This study highlights the robustness and variability of semantic priming across languages and provides a rich, linguistically diverse dataset for further analysis. The Stage 1 protocol for this Registered Report was accepted in principle on 15 July 2022. The protocol, as accepted by the journal, can be found at https://osf.io/u5bp6 (registration) or https://osf.io/q4fjy (preprint version 6, 31 May 2022).
© 2025. The Author(s), under exclusive licence to Springer Nature Limited.